AB0980 CASE-REVIEW ON FAMILIAL MEDITERRANEAN FEVER IN A SPECIALIZED CENTRE. (2nd June 2020) - Dos Santos Sobrín, R.; Martí Masanet, M.; Lopez-Montesinos, B.; Lacruz Pérez, L.; Calvo, I.
Abstract : Background: Familial Mediterranean Fever (FMF) is a genetic autoinflammatory disorder caused mostly by mutations in MEFV gene. Its inheritance is autosomal recessive and is the most frequent periodic fever syndrome. First-line treatment is based in colchicine use, so biologics (anti-IL-1) are reserved for refractory cases 1, 2 . Objectives: To account for clinic and treatment features of patients with FMF in a specialized center as opposed to non-referent centers. Methods: This study was developed in the Pediatric Rheumatology Service in Hospital Universitario y Politécnico La Fe de Valencia. Demographic, clinic and treatment data were collected from patients diagnosed of FMF since January 2004 to September 2019. Results: 106 patients met last FMF criteria 3 . 55% had a pathogenic mutation in genetic analysis. 52% were female. Before 10 years old, 71% of patients had the diagnosis (51% before 4 years old). Arthralgia/myalgia (73%), periodic fever (62%) and abdominal pain (54%) were the most common symptoms. Systemic Juvenile Idiopathic Arthritis (JIA, 6), other forms of JIA (9) and vasculitis (10) were the most prevalent comorbidities. When talking about treatment, 76, 4% received Colchicine (60, 5% with good response), 22, 6% needed a classical disease modifying antirheumatic drug (mostly Methotrexate) and 22 patients got biologic treatment (73% anti-IL-1). Conclusion: When analyzing this case-review, JIA has a strong association with our patients, so it could explain severe disease activity and more articular involvement. This could be an illustration to the higher use of Methotrexate. Also, the most relevant symptom was arthralgia while fever is the most frequent in literature. Likewise, age of diagnosis has been earlier than other case-series (this would be more frequent in other autoinflammatory syndromes, as literature relates) 1, 2, 4 . References: [1]Ozdogan H, Ugurlu S. Familial Mediterranean Fever. Presse Med. (2019). [2]Ozen S, Demirkaya E, Erer B, et al. EULAR recommendations for the management of familial Mediterranean fever. Ann Rheum Dis 2016;75:644-651. [3]Sag E, Demirel D, Demir S, et al. Performance of the new "Eurofever/PRINTO classification criteria" in FMF patients. Semin Arthritis Rheum. 2019;19:30369-5. [4]Rozenbaum M, Rosner I. Severe outcome of juvenile idiopathic arthritis (JIA) associated with familial Mediterranean fever (FMF). Clin Exp Rheumatol. 2004;22:S75-8. Disclosure of Interests: Raquel Dos Santos Sobrín: None declared, Miguel Martí Masanet: None declared, B Lopez-Montesinos: None declared, Lucía Lacruz Pérez: None declared, Inmaculada Calvo Grant/research support from: Bristol-Myers Squibb, Clementia, GlaxoSmithKline, Hoffman-La Roche, Merck Sharpe & Dohme, Novartis, Pfizer, Sanofi, Speakers bureau: AbbVie, GlaxoSmithKline, Hoffman-La Roche, Novartis